Sintok Forest Preservation Awareness (SiFPrA) Digital Medium Application (S/O 14570) - Abdul Salam, Sobihatun Nur; Harun, Harryizman; Annamalai, Subashini; Mohmad Yazam, Siti Syamsul Nurin; Saad, Mohd Nizam; Abdullah, Noor Aziah (UUM, 2021)
Forest preservation awareness is paramount from many aspects, namely science, culture, education. Studies about forest preservation awareness in Oxford forest (Mills, 2006), Alejico Carboniferous Forest (Fernández-Lozano & Gutiérrez-Alonso, 2017) and the dry forest in the northeast of Colombia (Rico-Bautista et al., 2019) have found that the digital medium applications are relevant and significant solutions in the digital transformation era. The digital solutions proposed were digital catalogued materials, digital album and also the forest information system. Based on the three studies reviewed, it is also noted that the effort to preserve the Sintok forest had not been made thus far, and the medium to preserve via mobile app and video documentary have not been achieved before. Therefore, this research aims to fill the gap by proposing to preserve Sintok forest's information via the mobile app and video documentary medium. ADDIE methodology is employed as the research methodology based on the justification that it is the most commonly used guide to develop an effective design in the instructional multimedia design field. The ADDIE methodology included several phases; analysis, design, development, implementation and evaluation (Aldoobie, 2017). Finally, the main outcome of this research is delivered which are SiFPrA (Sintok Forest Preservation Awareness) -Mobile AR (Augmented Reality) and SiFPrA -Video Documentary. Furthermore, this study has eventually helped towards culture and cultivated the Sintok forest preservation awareness of society by having the SiFPrA Competition. This competition has managed to have in total of 37 entries involving 111 participants from UUM students. It indirectly has shown that Sintok forest preservation awareness has gained well interest from UUM society and community.